The complete chloroplast genome sequence of Populus tremuloides (Salicaceae) - Li, Ang (Mitochondrial DNA B Resour, 2019)
The complete chloroplast genome sequence of Populus tremuloides was characterized from Illumina pair-end sequencing. The chloroplast genome of P. tremuloides was 155,816 bp in length, containing a large single-copy region (LSC) of 85,804 bp, a small single-copy region (SSC) of 16,489 bp, and two inverted repeat (IR) regions of 26,962 bp. The overall GC content is 36.71%, while the correponding values of the LSC, SSC, and IR regions are 64.9%, 69.2%, and 60.3%, respectively. The genome contains 167 complete genes, including 86 protein-coding genes (77 protein-coding gene species), 73 tRNA genes (29 tRNA species) and 8 rRNA genes(4 rRNA species). The Neighbour-joining phylogenetic analysis showed that P. tremuloides and Populus tremula clustered together as sisters to other Populus species.